Social Capital and Selectivity in Academic Co-Authorship Networks: the Case of Accounting Sciences in Brazil - João Estevão Barbosa Neto; Silvio Segundo Salej Higgins; Jacqueline Veneroso Alves da Cunha; Antônio Carlos Ribeiro (BBR: Brazilian Business Review)
Social capital has been mobilized as an explanatory variable in various empirical studies, but these studies have been unable to overcome the ambiguities inherent in a pre - scientific notion. The present study tests structural autonomy, one of the two established hypotheses on social capital, from the point of view of social network analysis. The test is a pplied in a case study of the academic co - authorship networks of accounting science programs in Brazil during the period from 2002 - 2010. The dynamics of selectivity present in this specific network, i.e., criteria of intertemporal choice, institutional end ogamy and mutual choice by productivity, were also analyzed. We observed that there were negative correlations between the authors’ constraints and their academic productivity indices, cascading intertemporal choices and endogamous choices according to ins titutional and productivity criteria.